Changes in Underwater Noise and Vessel Traffic in the Approaches to Halifax Harbor, Nova Scotia, Canada - Breeze, Heather; Li, Shihan; Marotte, Emmaline C.; Theriault, James A.; Wingfield, Jessica; Xu, Jinshan (Frontiers in Marine Science, 2021)
Researchers at Fisheries and Oceans Canada (DFO) initiated an acoustic monitoring project in Nova Scotia, Canada to investigate baleen whale presence and assess levels of underwater noise at selected coastal sites across the province. These sites had passive acoustic monitors (PAMs) in place during the onset of COVID-19 pandemic-related restrictions that had the potential to affect global shipping activity. To investigate if noise levels changed after restrictions were put in place, we analyzed and compared the acoustic data collected from March 28 to April 28 and August 6 to October 22 in both 2019 and 2020 from a site located in the approaches to the Port of Halifax, one of Canada’s major ports. We also investigated possible changes in vessel traffic from February 1 through April 28 and July 1 through July 28 in 2019 and 2020 using terrestrial-based Automatic Identification System (AIS) data provided by the Canadian Coast Guard and cargo information provided by the Port of Halifax. The acoustic data were analyzed in 1/3 octave frequency bands. For the 89.1 to 112 Hz frequency band, we found an 8.4 dB increase in the daily minimum sound pressure level (SPL) in April 2020 compared to April 2019 due the presence of a large crane vessel stationed near the mooring site. For the period of August to October, we found an approximately 1.7 dB reduction in the same metric from 2019 to 2020. The most noticeable change in vessel composition was the dramatic decrease in the number and occurrence of pleasure craft in July 2020 compared to the same period in 2019. While this analysis looked at only a single PAM and a limited amount of data, we observed changes in sound levels in the frequency band known to be associated with shipping as well as changes in vessel traffic; we conclude that these observed changes may be related to pandemic restrictions.